How Can a Blended Learning Environment Enhance Job-Related Competencies of In-Service Physical Educators? -Development and Implementation of a Web-Based Video Analysis Service (EQUEL) - Thomas Borchert; Ralf Schloeffel (European Teacher Education Network, 2017)
A web-based video analysis service (EQUEL) will be developed with the aim of encouraging in-service physical education (PE) teachers to reflect on their own teaching practice and how they can develop it further. Moodle® will enable their access to a web-based library with short authentic PE video sequences. By using the log files and user data from PE teachers, this database will be scientifically supervised and evaluated. The monitoring is marked by a strong orientation towards the desires of educational policy and practice in the federal state of Brandenburg and will be based on an educational design research (EDR) approach.